Southern Ocean Cloud Properties Derived From CAPRICORN and MARCUS Data. Issue 4 (23rd February 2021) - Mace, Gerald G.; Protat, Alain; Humphries, Ruhi S.; Alexander, Simon P.; McRobert, Ian M.; Ward, Jason; Selleck, Paul; Keywood, Melita; McFarquhar, Greg M.
Abstract: The properties of Southern Ocean (SO) liquid phase non precipitating clouds (hereafter clouds) are examined using shipborne data collected during the Measurements of Aerosols, Radiation and Clouds over the Southern Ocean and the Clouds Aerosols Precipitation Radiation and atmospheric Composition Over the SoutheRN ocean I and II campaigns that took place south of Australia during Autumn 2016 and Summer 2017–2018. Cloud properties are derived using data from W‐band radars, lidars, and microwave radiometers using an optimal estimation algorithm. The SO clouds tended to have larger liquid water paths (LWP, 115 ± 117 g m −2 ), smaller effective radii ( r e, 8.7 ± 3 μm), and higher number concentrations ( N d, 90 ± 107 cm −3 ) than typical values of eastern ocean basin stratocumulus. The clouds demonstrated a tendency for the LWP to increase with N d presumably due to precipitation suppression up to N d of approximately 100 cm −3 when mean LWP decreased with increasing N d . Due to higher optical depth, cloud albedos were less susceptible to changes in N d compared to subtropical stratocumulus. The highest latitude clouds of the datasets, observed along and near the Antarctic coast, presented a distinctly bimodal character. One mode had the properties of marine clouds further north. The other mode occurred in an aerosol environment characterized by high cloud condensation nuclei concentrations and elevated sulfate aerosol without obvious continental aerosol markers. These regions of higher cloud condensation nuclei tended to have higher N d, smaller r e and higher LWP suggesting sensitivity of cloud properties to seasonal biogenic aerosol production in the high latitude SO. Key Points: The properties of liquid Southern Ocean (SO) clouds vary with latitude SO low clouds are susceptible to aerosol concentrations SO clouds near Antarctica have high droplet numbers compared to lower latitude SO clouds